Correlation between Vertical Dimension of Occlusion and Different Facial Measurements among a Sample of Sudanese Adults. - Nmariq Mohammad Sultan; Ibrahim Ahmed Ismail (Universidad de Concepción., 2022)
Aim: This study aimed to evaluate the correlation between vertical dimension of occlusion (VDO) and various facial measurements in a sample of Sudanese adults. Material and Methods: A total of 113 dental students (33 males and 80 females) with a mean age of 21.7±1.26 years were enrolled in this study. Different facial measurements including (Eye-Mouth, Eye-Eye, Eye-Ear, and Ear Height) were compared with two different measurements of VDO: N-Gn (from the tip of the nose to the tip of the chin), and Sn-Me (from the base of the nose to the bottom of the chin). Pearson's correlation coefficient test was utilized for the correlation between the measured parameters. A p-value of less than 0.05 was considered significant for all analyses. Results: A significant positive correlation was shown between all measured facial distances and both measured VDO distances. Though, the strongest correlation was seen for the eye-mouth distance (r= 0.725, p<0.001), while the weakest was for ear height (r= 0.254, p= 0.007). A paired t-test revealed a significant longer N-Gn distance than Sn-Me distance. Also, it has been shown that there were no significant differences between right and left sides of the face. Conclusion: The distance measured from the outer canthus of the eye to the angle of the mouth can be used to predict Subnasale-Menton (Sn-Me) distance.